1992
DOI: 10.1111/j.1439-037x.1992.tb01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Losses and Utilization of Nitrogen by Sorghum as Affected by the Depth of a Swelling Clay Soil

Abstract: Chromusterts and Pellusterts located in India represent 20 % of the 257 million ha of Vertisols found worldwide. These soils are commonly associated with soils that exhibit vertic characteristics, such as Ustochrepts and Ustropepts, but that are too shallow (< 50 cm) to be classified as Vertisols; India has 20 million ha of such soils. Nitrogen is generally deficient in these soils, irrespective of their depth. N response of sorghum on the Vertisols is good even under rainfed conditions. Over a period of 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Whereas, in an actual field situation with a growing crop, extent of leaching of applied NO 3 would have been substantially reduced because of plant uptake. However, earlier at ICRISAT center, from a field experiment on a shallow Vertic Ustochrept (mean depth 0.45 m) with sorghum crop, Hong et al [6] have reported N losses as high as 61% of the applied KNO3 in a less wet year (1984) having a rainfall of 485 mm (June -September), than 1992, with 568 mm rainfall. Although they did not make direct measurements of N losses, howev-er, they explained that such losses were presumably through leaching because of shallow depth of the soil and intense rainfall following fertilizer application.…”
Section: Bromide Movementmentioning
confidence: 99%
“…Whereas, in an actual field situation with a growing crop, extent of leaching of applied NO 3 would have been substantially reduced because of plant uptake. However, earlier at ICRISAT center, from a field experiment on a shallow Vertic Ustochrept (mean depth 0.45 m) with sorghum crop, Hong et al [6] have reported N losses as high as 61% of the applied KNO3 in a less wet year (1984) having a rainfall of 485 mm (June -September), than 1992, with 568 mm rainfall. Although they did not make direct measurements of N losses, howev-er, they explained that such losses were presumably through leaching because of shallow depth of the soil and intense rainfall following fertilizer application.…”
Section: Bromide Movementmentioning
confidence: 99%